(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2021)
Comparative literature study is a theoretical study that can be applied to compare literary works, such as folklore. Folklore that has developed in society from generation to generation is a very interesting object to study. This study aims to compare the motives between the folklores of ‘Jaka Tarub and Nawang Wulan’ with ‘Niúláng Zhinü.’ The data of this research are taken from the stories of Jaka Tarub and Nawang Wulan as well as Niúláng Zhinü. This research uses a structural approach theory. The method used in this study is a qualitative descriptive method with a literary comparison technique. The object of study in this research is the story of Jaka Tarub and Nawang Wulan with the story of Niúláng Zhinü. The results of this study show that there are five similarities between the motifs of the two folklores, namely mythological, magic, tests, fraud, rewards and punishments. Meanwhile, in the story of Niúláng Zhinü, there are two additional motifs, namely animal motifs and miracles.